1978
DOI: 10.1152/jappl.1978.45.5.791
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial metabolism and performance in hypoxia: effect of epinephrine

Abstract: Effects of epinephrine (10(-5) M) on mechanical performance, glycolysis, glycogenolysis, lipolysis, and metabolism of adenine nucleotides were studied in isolated hypoxic rabbit hearts. The exposure of hearts to hypoxia decreased their mechanical performance and heart rate, but increased their utilization of glucose by 50% and the release of lactate by 139%. Myocardial stores of glycogen and ATP declined by 53 and 84%, respectively, but their breakdown products such as lactate, pyruvate, AMP, and inosine accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Maintenance or even slight increases in cardiac function during hypoxia are findings consistent with those published by previous investigators when employing ventilated sheep as a model (17,25). However, dissociation of functional parameters from myocardial intracellular phosphate levels as occurred during this study is fairly specific to the particular study conditions (2,(26)(27)(28). Intracellular phosphate as well as pH have been implicated as regulators of contractile function during hypoxia or ischemia (24,27,29).…”
Section: F102(%)supporting
confidence: 88%
See 1 more Smart Citation
“…Maintenance or even slight increases in cardiac function during hypoxia are findings consistent with those published by previous investigators when employing ventilated sheep as a model (17,25). However, dissociation of functional parameters from myocardial intracellular phosphate levels as occurred during this study is fairly specific to the particular study conditions (2,(26)(27)(28). Intracellular phosphate as well as pH have been implicated as regulators of contractile function during hypoxia or ischemia (24,27,29).…”
Section: F102(%)supporting
confidence: 88%
“…In contrast, decreases in Pi occur independently of pH, but are not associated with myocardial contractile depression in the present model studied in vivo. Previously, dissociation of cardiac function and intracellular phosphate concentration has been noted only in myocardium receiving substantial adrenergic stimulation during hypoxia or ischemia (28,31). This has occurred during catecholamine stimulation in hypoxic buffer-perfused hearts (28), and regionally ischemic myocardium in vivo (31).…”
Section: F102(%)mentioning
confidence: 99%
“…Although this study demonstrated a relation between pulmonary function and labile muscle fuels, it would be fortuitous if the biochemical changes described reflected the state of the contractile machinery (or degree of fatigue) of the intercostal muscles. There is convincing evidence that increasing work (4,16,(34)(35)(36), and decreasing oxygen (37) predictably decrease muscle ATP, PC, and glycogen, with a corresponding increase in lactate. This combination was present in 13 of 52 biopsy specimens, most commonly in the EXT specimens.…”
Section: Resultsmentioning
confidence: 99%